Bioinformatic approach of propolis as an inhibitor of peptidoglycan glycosyltransferase to improve antibacterial agent: An in-silico study - Imelia Arifatus Sani; Siska Maulidina Cahyani; Safira Fariha; O. Oliresianela; D. Diah (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2021)
Background: In Indonesia, the prevalence of dental and oral problems is still high at 57.6% in 2018, especially periodontitis at 74.1%. Peptidoglycan is an essential component of the bacterial cell wall. Peptidoglycan glycosyltransferase (PGT) is a protein target that plays a role in transferring lipid disaccharides II to growing glycan chains for bacterial cell wall synthesis. Propolis is a natural ingredient produced by bees and has anti-inflammatory, antibacterial, antiviral and antioxidant properties so that it has the potential to be a natural mouthwash ingredient. One of the antibacterial properties of propolis is to be able to kill and reduce the number of bacteria that cause periodontitis. Purpose: This study aims to investigate the potential of a specific compound of propolis as an inhibitor of protein peptidoglycan glycosyltransferase through bonding interactions. Methods: The method used is an in-silico test in molecular docking with computational software, namely Molegro virtual docker and Discovery Studio visualizer. Results: This study showed the types of bonds between the four compounds, and chlorhexidine as a control showed similar types of bonds, including hydrogen bonds, hydrophobic interactions and unfavourable bonds. The binding energy values of each of the five compounds were pinocembrin -222.166 kJ/mol, hesperetin -230.144 kJ/mol, chrysin -219.45 kJ/mol, caffeic acid phenethyl ester -266.64 kJ/mol and chlorhexidine -362.71 kJ/mol. Conclusion: Caffeic acid phenethyl ester (CAPE) is the most significant potential as an inhibitor of protein peptidoglycan glycosyltransferase and chlorhexidine has the highest binding affinity than the four propolis compounds, followed by caffeic acid phenethyl ester in propolis in silico.